Need for improved diabetes support among people with psychiatric disorders and diabetes treated in psychiatric outpatient clinics: results from a Danish cross-sectional study. Issue 1 (25th January 2022) - Knudsen, Lenette; Hansen, Dorte Lindqvist; Joensen, Lene Eide; Wibaek, Rasmus; Benros, Michael Eriksen; Jørgensen, Marit Eika; Andersen, Gregers Stig
Abstract : Introduction: People with psychiatric disorders have increased risk of premature death partly due to diabetes. This study aims to explore the quality of diabetes care, diabetes management, diabetes support and well-being of people with psychiatric disorders and diabetes. Research design and methods: A total of 107 participants aged ≥18 years with diabetes and psychiatric disorders treated at psychiatric outpatient clinics in Denmark were recruited from August 2018 to June 2019. This descriptive cross-sectional study includes data from medical records on quality of diabetes care (eg, level and annual examination of hemoglobin A1c (HbA1c )) and questionnaires on diabetes management (measured on items from the Summary of Diabetes Self-Care Activities Scale and diabetes distress based on Problem Areas in Diabetes Scale (PAID-5)), diabetes support (no, some or high support from eight potential support persons and experience of care actions measured on items from Patient Assessment of Chronic Illness Care) and well-being (WHO 5-Item Scale and self-rated general health). Results: The mean age was 52 years, 56% were men, the mean body mass index was 31.9 kg/m 2, the median HbA1c was 53 mmol/mol (7.0%) and the mean blood pressure was 131/83 mm Hg. The proportion with annual measurements of HbA1c was 93%, blood pressure 80%, cholesterol 93%, foot examination 77% and eye examination 75%. Fifty-one per cent had high diabetes distress (PAID-5 score ≥8). Diabetologists and general practitioners (39% and 37%) were the health professionals most frequently reported to provide high diabetes support. Conclusions: This study highlights a need for improved diabetes support in people with psychiatric disorders and diabetes. Although a high proportion received appropriate diabetes care, we found high levels of diabetes distress, moderate levels of optimal self-management behaviors, low well-being and low diabetes support from psychiatric health professionals, while one-third of the population found it relevant to receive diabetes support from psychiatric health professionals.